Acciones de rehabilitación frente a la entrada de gas radón - Frutos Vázquez, B.; Olaya Adán, M.; Esteban Saiz, J. L. (Revista ALCONPAT, 2011)
The World Health Organization (WHO), and other international organizations in radiationprotection, classified the Radon gas as a pathological agent for users in buildings. Because of itsorigin, in the decay chain of uranium, radioactive effects involve increasing risk of lung cancer.Originated from soils having granite or other substrates bearing uranium, it penetrates thosecommon construction materials, such as concrete slabs, basement walls, etc. Various routes can beconsidered to prevent the entry of Radon in inhabited spaces in existing buildings. An experimentalmodule of housing was built for this investigation, analyzing the radon concentrations. Theatmospheric pressure was correlated and identified as a determining parameter in flow variation inradon into a building without protection. Protective measures were then implemented asrehabilitation actions based on soil depressurization systems. These systems have used sumps intwo different locations and two types of extraction, forced or natural. The results show greatereffectiveness in the sump under slab, using natural or forced extraction, and high effectiveness ofthe outer sump, only under forced extraction. Effectiveness in the range of 91-99 % were achievedin all cases except in the outer sump with natural extraction that reached an average of 55 %